Synthesis, characterization and pharmacokinetic studies of 4-(3-aryl-1, 6-dihydro-6-iminopyridazin-1-yl)butanoic acid hydrochlorides (Journal of Bangladesh Academy of Sciences, 2021)
A series of six title compounds have been prepared using 3-amino- 6-chloropyridazine as starting material collected from commercial sources and were characterized by IR, 1H NMR, and high-resolution mass spectral (HRMS) data. The method involves three steps: Suzuki-Miyaura cross-coupling reaction, N(2)-alkylation, and acid hydrolysis, respectively, to obtain final products with good yields. According to Lipinski's rule of five and Veber's rule, pharmacokinetics studies of the synthesized compounds showed that all the parameters were in between the permissible limits. The toxicity parameters were low for the compounds to act as drugs.J. Bangladesh Acad. Sci. 45(1); 37-47: June 2021